2018
DOI: 10.1063/1.5041453
|View full text |Cite
|
Sign up to set email alerts
|

Conformationally averaged iterative Brownian dynamics simulations of semidilute polymer solutions

Abstract: The dynamics of semidilute polymer solutions are important to many polymer solution processing techniques such as fiber spinning and solution printing. The out-of-equilibrium molecular conformations resulting from processing flows directly impact material properties. Brownian dynamics (BD) simulations are a standard technique for studying this connection between polymer conformations in solution and processing flows because they can capture molecular-level polymer dynamics. However, BD simulations of semidilut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 63 publications
2
21
1
Order By: Relevance
“…The CA method approaches the full BD simulation upon another iteration w = 2, indicating the errors in the w = 1 iteration arise from conformationally averaging the Brownian noise over the While there is noise in the measurement, similar fluctuations are observed even in the dilute case and there is no observable trend in the error of the CA method. Solution stress is highly sensitive to preaveraging approximations, 14,19,75 so this is a promising result validating the accuracy of our CA approach.…”
Section: Transient Extension and Viscositysupporting
confidence: 58%
See 4 more Smart Citations
“…The CA method approaches the full BD simulation upon another iteration w = 2, indicating the errors in the w = 1 iteration arise from conformationally averaging the Brownian noise over the While there is noise in the measurement, similar fluctuations are observed even in the dilute case and there is no observable trend in the error of the CA method. Solution stress is highly sensitive to preaveraging approximations, 14,19,75 so this is a promising result validating the accuracy of our CA approach.…”
Section: Transient Extension and Viscositysupporting
confidence: 58%
“…While there are inherent approximations in the TEA, 67 we have previously shown that these lead to only small errors in the static polymer size and do not alter dynamic properties relative to simulations using the Krylov subspace. 75 We expect the method to match best in this case as shown by theory and our previous simulations, 74,75 which focus on steady state dynamics. We consider the ensemble average fractional extension projected along the axis of flow extension, ∆x f /L = (max({x i }) − min({x i }))/L, where L is the contour length.…”
Section: A Verification Of the Ca Methodsmentioning
confidence: 69%
See 3 more Smart Citations